DIKOTOMI PEMERINTAH DAERAH DAN MASYAARAKAT ADAT LOKAL DALAM UPAYA PEMBANGUNAN BUMI PERKEMAHAN DI TAMAN HUTAN RAYA ABDUL KABUPATEN SINJAI - Putra, Muh Aidil (Gemi: Jurnal Penelitian dan Pengabdian, 2024)
The purpose of this writing is to read the problem of conflict by looking at two regulations of the Minister of Forestry of the Republic of Indonesia regarding types of business plans and/or activities that must have an analysis of environmental impacts and guidelines for business activities for utilizing natural tourism environmental services in protected forests. This writing uses secondary data, namely the Regulation of the Minister of Forestry of the Republic of Indonesia in 2012, the webinar on the campground controversy in Tahura Abdul Latif, Sinjai Regency, 15 October 2020. The results of this research are that conflict between the government and local communities occurs when there is harmony between applicable policies and values. value that should occur. Legally, the construction of a campground is something that is legal considering that the legal basis is clear and must have an environmental impact analysis. However, the implementation is actually inversely proportional and the parties who suffer the most are local indigenous communities considering the impact of environmental damage which is felt directly.